Pengaruh Kualitas Produk, Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan - Muhammad Luthfi Rizky; Hijriyantomi Suyuthie (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
The research motivation by the phenomena about price, customer satisfaction, product and service quality, and quality at Cafe Pandeka Batusangkar. The research purpose is to investigate the relationship between price, service quality, product quality, and customer satisfaction at Cafe Pandeka Batusangkar. To investigate cause and effect, this kind of research combines a quantitative causal associative approach with a survey method. Customers of Cafe Pandeka Batusangkar make up the population. In this study, 301 respondents were sampled through purposive sampling, a non-probability sampling methodology. The questionnaire used to gather the data is valid and reliable. The study data were processed using SPSS 26.00. Based to the research results, there is no significant correlation from pricing and satisfaction of customer, service quality and satisfaction of customer, and product quality and satisfaction of customer.